Protection of Turbidity on Reefs along the Southeast Coast of the Kalimantan during the 2015 El Niño - Suhaili Asmawi; Muhammad Ahsin Rifa'i; Idiannor Mahyudin; Muhammad Ruslan (Journal of Wetlands Environmental Management, 2020)
Coral reef, the most diverse and highly valuable marine ecosystem, may be influenced by bleaching. This study aimed to determine the effect of turbidity on the severity of coral bleaching and mortality due to thermal stress and high solar irradiation caused by the 2015 El Niño event. Coral colonies in eighteen permanent bleaching belt transects (50 m x 1 m) in six sites were observed from June to November 2015, coinciding with the 2015 El Niño event. Environmental factors: water depth, sea surface temperature (SST), salinity, turbidity, sedimentation and total suspended solid (TSS) were measured on the same transect. The results of the study showed that the 2015 El Niño event was a major disaster for reefs on the southeast coast of the Kalimantan. Of total colonies (N = 12,954), 45.4% of colonies were bleached and 14.7% of colonies died during the period of July to November 2015. Turbidity, TSS, and sedimentation were negatively correlated with the bleaching mortality index (BMI). Coral bleaching in clear and deep waters occurred earlier and increased rapidly compared to that in turbid waters. However, the severity of coral bleaching in the turbid zone increased dramatically when the turbidity dropped to <3 NTU. Turbidity >5 NTU could provide shade, in which the proportion of dead corals was only 3.5%. The severity of coral bleaching in the turbid zone is not solely due to thermal stress and solar irradiation; it may also be influenced by a history of exposure to high turbidity and low salinity.